Errors at the treatment of elbow joint fractures with dislocations - Matelenok, Ievgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Among the injuries of the elbow the fractures with dislocations are the most challenging with a significant number of unsatisfactory results and complications. In addition to the severity of the damage, failed results are associated with errors in diagnosis and treatment. Objective: to study retrospectively the structure and causes of errors those occur during the diagnosis and treatment of fractures with dislocations of the elbow joint. Methods: clinical materials were analyzed for 110 patients with fracture with dislocation, 80 of them were admitted into Sytenko Institute of Spine and Joint Pathology and from other medical institutions (81 ± 19) days after the injury. A retrospective analysis was carried out. We evaluated the accuracy of diagnoses for the site fractures; determine the state of its stability after injury in 4 degrees: stability, relatively stability, instability and very instability; the conformity of therapeutic tactics and the quality of its implementation. Results: 74 % of mistakes were attributable to the assessment of the degree of loss of stability of the injured joint and led to inadequate curative tactics. Of the 23 injured patients 17 were treated with conservative therapy instead of the required surgical treatment. Errors in surgical treatment (6 patients) are associated with inappropriate volume of surgery and failed osteosynthesis. There was an opposite relationship between the timing of surgery for the adverse effects of injuries and the long-term results of treatment (Pearson coefficient –0.48; p < 0.05). Conclusions: most of the errors were associated with wrong diagnosis that led to the incorrect assessment of the degree of instability of the injured joint and wrong selection of false therapeutic tactics. Correction of medical tactics even at the stage of formation of unsatisfactory consequences of injuries increases the likelihood of obtaining favorable results.